2012
DOI: 10.1093/nar/gks033
|View full text |Cite
|
Sign up to set email alerts
|

In vivo screening of modified siRNAs for non-specific antiviral effect in a small fish model: number and localization in the strands are important

Abstract: Small interfering RNAs (siRNAs) are promising new active compounds in gene medicine but the induction of non-specific immune responses following their delivery continues to be a serious problem. With the purpose of avoiding such effects chemically modified siRNAs are tested in screening assay but often only examining the expression of specific immunologically relevant genes in selected cell populations typically blood cells from treated animals or humans. Assays using a relevant physiological state in biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Recent in vitro ( Sarathi et al, 2008 ) and in vivo ( Sarathi et al, 2010 ) studies have demonstrated promising results for using RNAi to combat white spot syndrome virus (WSSV), which is an aquatic viral disease of shrimp. Similarly, several in vitro ( Ruiz et al, 2009; Kim and Kim, 2011; Kim et al, 2012 ) and in vivo ( Schyth et al, 2007, 2012; Bohle et al, 2011 ) studies have tested controlling a fish viral disease, termed viral hemorrhagic septicemia virus (VHSV), by RNAi. For this study, the feasibility of using short double stranded RNAs termed small interfering (si)RNAs was tested to inhibit in vitro viral replication of CyHV-3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vitro ( Sarathi et al, 2008 ) and in vivo ( Sarathi et al, 2010 ) studies have demonstrated promising results for using RNAi to combat white spot syndrome virus (WSSV), which is an aquatic viral disease of shrimp. Similarly, several in vitro ( Ruiz et al, 2009; Kim and Kim, 2011; Kim et al, 2012 ) and in vivo ( Schyth et al, 2007, 2012; Bohle et al, 2011 ) studies have tested controlling a fish viral disease, termed viral hemorrhagic septicemia virus (VHSV), by RNAi. For this study, the feasibility of using short double stranded RNAs termed small interfering (si)RNAs was tested to inhibit in vitro viral replication of CyHV-3.…”
mentioning
confidence: 99%
“…The subtle differences detected by qPCR may explain differential in vivo survival rates observed in TK deletions ( Costes et al, 2008 ). The siRNAs used in this trial were unmodified and are known to be effective for a limited time after transfection ( Schyth et al, 2012 ). The transient nature of siRNA inhibition can be enhanced by chemical modifications to siRNAs ( Schyth et al, 2012 ) or the use of longer dsRNA (27/25 mer) that are cellular substrate targets for dicer ( Bohle et al, 2011 ).…”
mentioning
confidence: 99%
“…This indicates that mixing siRNAs which target different viral genes could be the most promising approach for a treatment of CyHV-3. However, the treatment of cells with siRNAs and its modifications may induce a type I IFN response in cells (Schyth et al 2012), which can be responsible for the observed reduction in CyHV-3 replication rather than the silencing of CyHV-3 genes by the siRNA oligonucleotides. This concern is supported by our data (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical modifications of siRNAs (Schyth et al . 2012 ) or the use of longer dsRNA (27/25 mer) that is a cellular substrate target of dicer (Bohle, Lorenzen & Schyth 2011 ) provide for alternative methods to study the in vivo effects of siRNA knock-down. Although current EPC lineages are contaminated with cells from another cyprinidae, fathead minnow Pimephales promelas (Winton et al .…”
Section: Discussionmentioning
confidence: 99%